Haida stories and beliefs [electronic resource] - Hill-Tout, Charles, 1858-1944 ([London : Spottiswoode, 1898)
Running title: Report, 1898, on the ethnological survey of Canada. Includes brief pieces in the Haida language. At head of title: Appendix I. Electronic reproduction. Mode of access: Internet. 44